Pharmaceutical Aspects of the Recombinant Human Serum Albumin Dimer: Structural Characteristics, Biological Properties, and Medical Applications - Taguchi, K.; Chuang, Victor; Maruyama, T.; Otagiri, M. (John Wiley & Sons Inc, 2012)
Human serum albumin is the most abundant protein in the blood. It is clinically used in the treatment of severe hypoalbuminemia and as a plasma expander. The use of albumins as a carrier for drugs is currently being developed, and some are now in the preclinical and clinical trial stages. The main technologies for utilizing an albumin as a drug carrier are protein fusion, polymerization and surface modification, and so on. Among these technologies, albumin dimerization has wide clinical applications as a plasma expander as well as a drug carrier. Despite the fact that many reports have appeared on drugs using an albumin dimer as a carrier, our knowledge of the characteristics of the albumin dimer itself is incomplete. In this review, we summarize the structural characteristics of recombinant albumin dimers produced by two methods, namely, chemical linkage with 1,6-bis(maleimido)hexane and genetically linked with an amino acid linker, and the physicochemical characteristics and biological properties of these preparations. Finally, the potential for pharmaceutical applications of albumin dimers in clinical situations is discussed.